Affected other interventions: a systematic review and meta‐analysis across addictions. (21st February 2022) - Merkouris, Stephanie S.; Rodda, Simone N.; Dowling, Nicki A.
Abstract: Background and Aims: Individuals impacted by someone else's alcohol, illicit drug, gambling and gaming problems (affected others) experience extensive harms. To our knowledge, this is the first systematic review and meta‐analysis to determine the effectiveness of psychosocial interventions delivered to affected others across addictions. Methods: This review adhered to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses. An electronic database search (PsycInfo, Medline, Cinahl and EMBASE) of randomized controlled trials (RCTs) published until August 2021 was conducted. RCTs with passive control groups, evaluating psychosocial tertiary interventions delivered to affected others of people with addictions (problematic alcohol use, substance use, gambling or gaming) that did not require the involvement of the addicted person, were included. Results: Twenty included studies, published in 22 articles, mainly evaluated interventions for alcohol use, followed by gambling and illicit drugs, with none investigating gaming interventions. The interventions mainly targeted partners/spouses and focused upon improving affected other outcomes, addicted person outcomes or both. Meta‐analyses revealed beneficial intervention effects over control groups on some affected other (depressive symptomatology [standardized mean difference (SMD) = −0.48, 95% confidence interval (CI) = −0.67, –0.29], life satisfaction (SMD = −0.37, 95% CI = −0.71, −0.03) and coping style (SMD = −1.33, 95% CI = −1.87, –0.79), addicted person [treatment entry, risk ratio (RR) = 0.86, 95% CI = 0.75–0.98] and relationship functioning outcomes (marital discord, SMD = −0.40, 95% CI = −0.61, −0.18) at post‐intervention. No beneficial intervention effects were identified at short‐term follow‐up (4–11 months post‐treatment). The beneficial intervention effects identified at post‐treatment remained when limiting to studies of alcohol use and therapist‐delivered interventions. Conclusions: Psychosocial interventions delivered to affected others of people with addictions (problematic alcohol use, substance use, gambling or gaming) may be effective in improving some, but not all, affected other (depression, life satisfaction, coping), addicted person (treatment) and relationship functioning (marital discord) outcomes for affected others across the addictions, but the conclusion remains tentative due to limited studies and methodological limitations.